2015
DOI: 10.1093/icvts/ivv309
|View full text |Cite
|
Sign up to set email alerts
|

Video-assisted thoracoscopic surgery versus open thoracotomy in pulmonary metastasectomy: a meta-analysis of observational studies

Abstract: VATS is an alternative surgical approach for pulmonary metastasectomy in patients with resectable pulmonary metastases. Further large prospective studies are needed to identify the indications for VATS in patients with pulmonary metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 25 publications
3
28
0
3
Order By: Relevance
“…Data comparing operative techniques for pulmonary metastasectomy in other tumor types suggest comparable outcomes but may not be transferable to osteosarcoma. A recent systematic review of metastasectomy in all tumor types found superior 5‐year overall and recurrence‐free survival with the thoracoscopic approach, 25 and a meta‐analysis published in 2015 showed similar results 26 . However, metastases from other sarcomas lack the calcification of osteosarcoma which allows for manual palpation at sizes below the resolution of CT.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Data comparing operative techniques for pulmonary metastasectomy in other tumor types suggest comparable outcomes but may not be transferable to osteosarcoma. A recent systematic review of metastasectomy in all tumor types found superior 5‐year overall and recurrence‐free survival with the thoracoscopic approach, 25 and a meta‐analysis published in 2015 showed similar results 26 . However, metastases from other sarcomas lack the calcification of osteosarcoma which allows for manual palpation at sizes below the resolution of CT.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review of metastasectomy in all tumor types found superior 5-year overall and recurrence-free survival with the thoracoscopic approach, 25 and a meta-analysis published in 2015 showed similar results. 26 However, metastases from other sarcomas lack the calcification of osteosarcoma which allows for manual palpation at sizes below the resolution of CT. pain, as well as shorter ICU and hospital stays. 13,16,[29][30][31] Notably, prior studies have demonstrated a profound difference in the risk of scoliosis after thoracotomy (54%) or thoracoscopy (9%), although the use of muscle-sparing techniques for thoracotomy may help to mitigate this risk.…”
Section: Discussionmentioning
confidence: 99%
“…Colorectal adenocarcinoma was the most prevalent primary extra-thoracic cancer. The previously treated extra-thoracic malignancies were colorectal (16), breast (8), urogenital (7), sarcoma (5) All resected specimens included the microcoils which were confirmed with fluoroscopy during surgery and on x-rays postresection. Video-assisted thoracoscopic surgery wedge resection after CTML was successfully diagnostic in 98% of the patients.…”
Section: Resultsmentioning
confidence: 99%
“…15 Further, several metaanalyses confirmed no difference in survival between VATS and conventional thoracotomy for treatment of pulmonary metastases, making VATS a safe and feasible option. 16 Unfortunately, the initial management options of lung nodules in patients diagnosed with cancer are usually limited by lesion size. Small nodules cannot be reliably classified as benign or malignant using CT criteria or PET/CT scan analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Zwar stellt die VATS das geringere Operationstrauma dar und führt im Vergleich mit der Thorakotomie zu einer statistisch signifikanten Reduktion postoperativer Komplikationen, der Thoraxchirurg muss jedoch fürchten, radiologisch nicht erkannte Lungenmetastasen zurückzulassen [8,27]. Im Gegensatz zu dieser Befürchtung legen aktuelle Studiendaten nah, dass die VATS das Gesamtüberleben, das krankheitsspezifische und das progressionsfreie Überleben im Vergleich zur Thorakotomie nicht signifikant reduziert [8,15,[27][28][29] [28]. Der Vergleich der operativen Zugangswege sollte zukünftig Gegenstand prospektiver Studien sein.…”
Section: Metastasenresektionunclassified